320 Starting a hipec programme in a low resource setting. (18th September 2019) - Peedicayil, A; Mittal, R; Joel, A; Rai, E; Sebastian, A; Thomas, V; Thomas, A; Chandy, R; Subramani, K
Abstract : Objectives: Hyperthermic IntraPeritoeneal Chemotherapy (HIPEC) after maximal cytroreduction is a promising modality of treating women with ovarian cancer. In order to determine the feasibility of setting up a HIPEC programme in India, we document our initial experience. Methods: Ethics Committee clearance was obtained to start the programme. The electronic medical records of all patients who underwent HIPEC in our department was reviewed. Results: A total of 14 patients underwent HIPEC in the first 2 years: one primary, 6 interval and 7 recurrent cytoreductions. The women had a mean age of 46.9 years (36 to 62), median performance score of 1 (o to 2) and a median peritoneal carcinomatosis index (PCI) of 10 (2 to 25). The histology was serous in 9, mucinous in 4 and endometrioid in one. Four patients had bowel resection of whom 2 had an end ileostomy and one had an end colostomy. The median duration of surgery was 9 hours (5 to 10) and the median completeness of cytoreduction score was 1 (0 to 2). The drugs used in HIPEC were Cisplatin and Oxaliplatin. The median duration of hospital stay was 9 days (6 to 21). Two patients were readmitted to hospital and 3 patients had re-laparotomy. The main complications were venous thromboembolism in one, bleeding in one and wound dehiscence in one. Conclusions: Cytoreductive surgery with HIPEC is feasible in a low resource setting with acceptable morbidity where the main limitations are non-availability of operating time and patient's ability to pay for treatment.